Partisipasi Politik Pemilih Disabilitas Dalam Pemilihan Gubernur Sumatera Barat Tahun 2020 Di Kota Padang - desy helda; Yohanis; Berian Hariadi (LPPM STISIP IMAM BONJOL, 2023)
This study aims to describe the political participation of people with disabilities in the general election of Governor and Deputy Governor of West Sumatra in 2020 and to determine the supporting factors and obstacles to political participation of people with disabilities in the election of Governor and Deputy Governor of West Sumatra. The type of research is descriptive qualitative which describes descriptively about the political participation of people with disabilities in the general election of Governor and Deputy Governor of West Sumatra in 2020. The sources of data are primary data and secondary data. The techniques of Data collection used are observation, interviews and documentation. In this study, there were main informants consisting of thirteen (13) voters from blind people. The Data analysis techniques by analyzing the results of the processed data are interpreted in the form of narration.